2022
DOI: 10.3390/agriculture12081242
|View full text |Cite
|
Sign up to set email alerts
|

Grape Cluster Real-Time Detection in Complex Natural Scenes Based on YOLOv5s Deep Learning Network

Abstract: Due to differences in planting environment, color, shape, size, and compactness, accurate detection of grape clusters is very difficult. Herein, a real-time detection method for grape clusters based on the YOLOv5s deep learning algorithm was proposed. More specifically, a novel dataset called Grape-internet was constructed, which consisted of 8657 grape images and corresponding annotation files in complex scenes. By training and adjusting the parameters of the YOLOv5s model on the data set, and by reducing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…In [14,32,33,43], only one or two classes were used as an output [44]. In relation to the more complex variations of the object of interest and the number of classes in our work, it can be concluded that the results obtained in this research are more significant because 5 classes are defined in our work and the results are promising: F1 as a measure of the proposed algorithm amounted to 92-97%, and the machine's current accuracy is 91-98%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In [14,32,33,43], only one or two classes were used as an output [44]. In relation to the more complex variations of the object of interest and the number of classes in our work, it can be concluded that the results obtained in this research are more significant because 5 classes are defined in our work and the results are promising: F1 as a measure of the proposed algorithm amounted to 92-97%, and the machine's current accuracy is 91-98%.…”
Section: Discussionmentioning
confidence: 99%
“…In [43], the authors highlighted the advantages of YOLOv5 in terms of lightweight and better real-time performance. However, YOLOv3 produced exactly the same results as YOLOv5 for F1, mAP, recall, and precision.…”
Section: Discussionmentioning
confidence: 99%
“…It can lead to data leakage if the train/validation/test split is performed after offline augmentation. This is the case in the work of Zhang et al [114] (10-fold oversampling before splitting).…”
Section: Performance Comparisonmentioning
confidence: 91%
“…Moreover, due to the limitation of hardware resources, adopting a lighter network is necessary. The different network configurations of YOLOv5 model are divided into YOLOV5 37 , YOLOv5m 38 , YOLOv5l 39 , and other structures, among which YOLOV5 model has the simplest structure, so it is considered.…”
Section: Introductionmentioning
confidence: 99%